Modeling privacy issues in distributed enterprise resource planning systems. (20th November 2014) - Misra, Subhas Chandra; Singh, Virender; Jha, Naveen Kumar; Bisui, Sandip
Summary: With extensive usage and dependence on communication networks, 'privacy' issues in enterprise distributed systems have become fundamentally important. Privacy concerns have flooded the market especially in the public domain, and with the changing environment of software usage and involvement of malicious substances associated with any network, it becomes essential to safeguard and ascertain privacy among users and incorporate the same safeguard to protect privacy in software as well. The methodologies and tools architecting distributed enterprise resource planning (ERP) systems are primarily new and are vulnerable to malicious attacks. This paper aims at identifying some of critical privacy issues by collecting data from ERP practitioners. This work models variables associated with ERP with the variables of privacy to establish a robust adoption of ERP practices. Privacy issues concerning ERP are listed. Several variables associated with the development, implementation, and control of ERP are identified in the existing literature. A questionnaire instrument was distributed among a set of ERP practitioners. The response data collected thereby were analyzed statistically. Based upon the statistical analysis, an attempt has been made in the paper to make a ranking of the privacy factors. The observations are discussed in detail, and some specific conclusions have been made. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : The prime objective of this work has been to determine the important factors that affect the privacy of enterprise resource planning systems. We undertook a survey‐based quantitative study approach by identifying the privacy factors from the perspective of software practitioners.